Evaluasi Keputusan Menteri Pendidikan Nasional No.234/U/2000 Tentang Pendirian Perguruan Tinggi (Studi Evaluasi Kepmendiknas No.234/U/2000 di Kopertis Wilayah VII Jawa Timur) - Yayuk Suci Rahayu (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2013)
The aims of the research are to evaluate and identify factors causing efficacy / failure of policy of Kepmendiknas No. 234/U/2000 about Guidance of Founding of College in its bearing with College Private sector growth in Regional Kopertis of VII East Java, and also to give recommendation proposal able to be used as by trouble-shooting alternative faced. As for method which is utilized in this research is deskriptip method qualitative. Research Obyek is College Private sector in Regional Kopertis environment of VII East Java, mostly stand up before publishing of Kepmendiknas No. 234/U/2000. Result of research indicate that the target of evaluation policy of this Kepmendiknas, namely make harmonization of physical science area and social science still not yet succeeded, other target namely quicken PTS independence from energy side also still not yet succeeded, is proven from situation of lecturer remain to amounting to 18.993 one holding who have lectureship academic position only 3.612 people ( 19,02%). While seen from titled education qualification of Magister only 4.355 people ( 22,93%), and only equal to 594 people ( 3,13%) which is have education to of Doctor ( S3). Comparison between physical science area group and social science area in the reality still less adequate. PTS motivation beside have social mission also have business mission / commercial, so that in decission making or consideration having the character of upper most economic progressively. Fund provided by College Private sector in general stem from student, this matter disagree with section 11 Kepmendiknas No. 234/U/2000, that source of defrayal of college provided by pertinent college organizer. The Head perception of the PTS which in form of University source of defrayal coming from student most coming from social science area group student. Keyword : Evaluation, Kepmendiknas No. 234/U/2000, Growth College Private sector